2019
DOI: 10.2319/060218-419.1
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal side effects of rapid and slow maxillary expansion: A systematic review

Abstract: Objectives: To identify the scientific evidence that demonstrates which of the transverse maxillary treatments has the least effect on periodontal tissues. Materials and Methods: PubMed (MEDLINE), Cochrane Library, Scopus, Web of Science, Virtual Health Library, Google Scholar, and OpenGrey were searched without restrictions. A hand search was also carried out in the reference lists of the articles selected. The related artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…The wearing of both expanders increased the transverse distances of premolars and molars, varying from 5.93 to 6.55 mm, similar to what has been reported elsewhere [22][23][24][25]. The tooth rotation varied from − 1.05 o to 1.77 o , without a specific direction for each type of expander and without a statistically significant difference between them, as reported in another study [27], in which tooth rotation was minimal and did not provoke any relevant clinical drawbacks.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The wearing of both expanders increased the transverse distances of premolars and molars, varying from 5.93 to 6.55 mm, similar to what has been reported elsewhere [22][23][24][25]. The tooth rotation varied from − 1.05 o to 1.77 o , without a specific direction for each type of expander and without a statistically significant difference between them, as reported in another study [27], in which tooth rotation was minimal and did not provoke any relevant clinical drawbacks.…”
Section: Discussionsupporting
confidence: 88%
“…According to systematic reviews published in recent years, scientific evidence on RPE is basically limited to the assessment of the effects of orthodontic expanders on hard and soft tissues of the stomatognathic system [22][23][24][25]. Researchers have not fully explored the impact of these interventions on the quality of life of individuals [11,14].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, relative to which device would be less harmful to periodontal tissues, a current systematic review concluded that there were no significant differences between the two expanders and considered the devices equally safe for oral health. 19 The proposed approach was firstly based on the gold standard protocol 9,10 by means of antibiotic therapy (amoxicillin) since the open ulcers served as a microbial reservoir, with the possibility of blood contamination. Moreover, the symptomatology presented by the patient (fever state, painful, prostration and very unwell condition) showed the clear signs of disseminated infection, making prescription mandatory in such cases.…”
Section: Discussionmentioning
confidence: 99%
“…For example, dental anchorage may cause buccal tipping, root resorption or extrusion of the anchor teeth, compression of the periodontal ligament, buccal bone resorption and bending of the alveolar bone during the distraction phase 3 . A systematic review evaluated periodontal side effects of rapid and slow maxillary expansion, and there were no significant differences which type of maxillary expansion has the least periodontal side effects 4 . Regarding the dental pulp, the expected changes include microcirculatory changes, pulpal blood flow interruption, haemorrhage, pulp calcifications 5,6 and odontoblastic degeneration and vacuolization of pulp tissues 7 .…”
Section: Introductionmentioning
confidence: 99%